(untitled) (Comparative & International Education Series, 2021)
This chapter explores the internationalization policy, programs, and initiatives at Historically Black Colleges and Universities (HBCUs) in the United States. The bigger questions that we wanted to investigate included: What does internationalization mean for HBCUs? How can internationalization be leveraged as a tool for social justice and diversity thus moving students who are often placed at the periphery of society to the center? How do we embed internationalization in the ethos of HBCUs institutional culture? What are the tensions between internationalization and while still serving who have been historically marginalized?